(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the changes of meteorological parameters in the irrigated areas of Fergana region during the autumn wheat vegetation period were studied on the basis of meteorological calculation and mathematical statistical methods. The maximum and minimum values of air temperature during the winter wheat vegetation period were calculated by five-day periods and gradations of transition from different levels. In the winter months (December-February), the temperature range of 0÷+5.0°С is 59.4-48.3% at Kokand station, 61.3÷49.0% at Fergana station, 62.7÷47.7% at Kuva station changes. Sudden changes in temperature values during the dormant period of the plant are considered a dangerous meteorological phenomenon, which does not allow the complete period of plant dormancy. This, in turn, can lead to a change in the period of development phases, a decrease in the number of bushes in the field.